A Cane for More than Walking: The Design of a Smart Cane for Physical Therapy. (September 2016) - Matalenas, Laura A.; Hu, Tengwen; Veeramachaneni, Vishnu; Muth, John
This paper discusses the user research and design process of the PTCane: a smart cane for physical therapy. The goal of the research process is to identify limitations in current home exercise programs, and the goal of the design process is to provide a device, the PTCane, to overcome these limitations and augment home exercise programs. User research included a general survey, physical therapy observations, and expert interviews. From our user research, we identified that the technology needs to overcome barriers to physical therapy, inform patients of their exercise accuracy, and decrease helplessness during recovery. The final proposed cane design includes reminders, an accuracy feedback system, a pain and progress survey, and a system to provide information about progress in therapy to both patients and therapists.